ANALYSIS OF COST MANAGEMENT MODELS TO ENSURE PRODUCT QUALITY - Kholboyeva Shokhsanam Abdumalik Kizi; Kasimov Akhtamhon Akramovych (Scholars Digest Publishing, 2024)
This article is about the analysis of cost management models to ensure product quality, the principle of reflecting the quality of the product as a product shows the relativity of division into product objects as the results of processes and processes as the ways to achieve these results.
Keywords: costs, technological processes, organizational factors, technical factors, economic factors, uncertainty, management models, cost, product quality.